Educational, Social and Economic Upliftment of the Backward Community and the Role of Mandal Commission: Examining the impact of the Mandal Commission on the empowerment of the backward community (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Mandal Commission plays a very significant role in theeducational, social and economic upliftment of the backward community. Briefaccount of the Mandal Commission is as follows:-